A plant‐specific HUA2‐LIKE (HULK) gene family in Arabidopsis thaliana is essential for development. (28th August 2014) - Jali, Sathya S.; Rosloski, Sarah M.; Janakirama, Preetam; Steffen, Joshua G.; Zhurov, Vladimir; Berleth, Thomas; Clark, Richard M.; Grbic, Vojislava
Summary In Arabidopsis thaliana, the HUA2 gene is required for proper expression of FLOWERING LOCUS C (FLC) and AGAMOUS, key regulators of flowering time and reproductive development, respectively. Although HUA2 is broadly expressed, plants lacking HUA2 function have only moderately reduced plant stature, leaf initiation rate and flowering time. To better understand HUA2 activity, and to test whether redundancy with similar genes underlies the absence of strong phenotypes in HUA2 mutant plants, we identified and subsequently characterized three additional HUA2‐LIKE (HULK) genes in Arabidopsis. These genes form two clades (HUA2/HULK1 and HULK2/HULK3), with members broadly conserved in both vascular and non‐vascular plants, but not present outside the plant kingdom. Plants with progressively reduced HULK activity had increasingly severe developmental defects, and plants homozygous for loss‐of‐function mutations in all four HULK genes were not recovered. Multiple mutants displayed reproductive, embryonic and post‐embryonic abnormalities, and provide detailed insights into the overlapping and unique functions of individual HULK genes. With regard to flowering time, opposing influences were apparent: hua2 hulk1 plants were early‐flowering, while hulk2 hulk3 mutants were late‐flowering, and hua2 acted epistatically to cause early flowering in all combinations. Genome‐wide expression profiling of mutant combinations using RNA‐Seq revealed complex transcriptional changes in seedlings, with FLC, a known target of HUA2, among the most affected. Our studies, which include characterization of HULK expression patterns and subcellular localization, suggest that the HULK genes encode conserved nuclear factors with partially redundant but essential functions associated with diverse genetic pathways in plants.